2005
DOI: 10.1063/1.1994852
|View full text |Cite
|
Sign up to set email alerts
|

Branching ratio deviations from statistical behavior in core photoionization

Abstract: Accurate calculations of carbon 1s photoionization cross sections have been performed at the density functional level with the B-spline linear combination of atomic orbitals approach. The molecules considered are FC[triple bond]CH, FC[triple bond]CCH3, FC[triple bond]CCN, F2C=CH2, CF3COOCH2CH3, and C3H5O. The variation of the branching ratios relative to inequivalent C 1s ionizations have been evaluated from threshold to about 100 eV photoelectron kinetic energy. Large deviations from the statistical ratios ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
1
12
1
Order By: Relevance
“…Such effects were predicted theoretically for carbon 1s ionization in a number of molecules by Di Tommaso and Decleva 9 and observed experimentally by Söderström et al in chlorine-substituted ethanes. 6 These results showed that there is an oscillatory behavior of the cross sections as the photon energy increases and that these oscillations can be seen several hundred eV above the ionization threshold.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…Such effects were predicted theoretically for carbon 1s ionization in a number of molecules by Di Tommaso and Decleva 9 and observed experimentally by Söderström et al in chlorine-substituted ethanes. 6 These results showed that there is an oscillatory behavior of the cross sections as the photon energy increases and that these oscillations can be seen several hundred eV above the ionization threshold.…”
Section: Introductionsupporting
confidence: 54%
“…is predicted to be a common feature for substituted ethyne molecules such as FCCH, FCCCH 3 , and FCCCN. 9 The origin of this feature is the presence of a continuum σ * u resonance, associated with the ionization of the σ C2C3 antibonding orbital, similar to that seen in the core ionization of N 2 . Such a feature also appears in the 1a 1 ionization, but with much reduced intensity, because of the smaller dipole transition moment from the adjacent methyl C1s orbital.…”
Section: Density Functional Modelmentioning
confidence: 92%
See 2 more Smart Citations
“…The theoretical β parameters for chloroethanes and the ESCA molecule are available in the literature only for relatively low kinetic energies up to 300 and 100 eV, respectively, where asymptotic limits are not reached yet. 45,49 To estimate the correction factor at high energies, we have calculated β parameters up to electron kinetic energies 570 and 530 eV for chloroethanes and the ESCA molecule, respectively. The details of the calculations are to be discussed below.…”
Section: Data Treatmentmentioning
confidence: 99%